Assessment of clinical outcomes of Roth and MBT bracket prescription using the American Board of Orthodontics Objective Grading System - Mahesh Jain; Joseph Varghese; Rohan Mascarenhas; Subraya Mogra; Siddarth Shetty; Nidhi Dhakar (Contemporary Clinical Dentistry, 2013)
Background: There is always a need to assess whether small changes in bracket prescription can lead to visually detectable differences in tooth positions. However, with little clinical evidence to show advantages of any of the popularly used bracket systems, orthodontists are forced to make clinical decisions with little scientific guidance. Aim: To compare the orthodontic cases finished with Roth and MBT prescription using American Board of Orthodontics-Objective Grading System (ABO-OGS). Settings and Design: Department of Orthodontics, Post-graduate dental college, retrospective cross-sectional study. Materials and Methods: Forty patients selected were divided into two groups of 20 patients each finished with straight wire appliance using Roth and MBT prescription, respectively. The examiner ability was assessed and calibrated by one of the ABO certified clinician to grade cases using the OGS. Statistical Analysis: Unpaired student t-test was used and P < 0.05 was accepted as significant. Results and Conclusions: MBT bracket group had a lower score of 2.60 points in buccolingual inclination and lower score of 1.10 points in occlusal contact category that was statistically significant when compared with Roth group. The difference in total ABO-OGS score was 2.65 points showing that the outcome for the MBT prescription was better than that of the Roth prescription, which is statistically significant, but with little or no clinical significance. It can be concluded that use of either one of the Roth and MBT bracket prescriptions have no impact to the overall clinical outcome and quality of treatment entirely depends on clinician judgment and experience.